AN AYURVEDIC APPROACH FOR BALANOPOSTHITIS – A CASE STUDY - Chander Shekhar Sharma,; Amrita Sharma, (International Journal of Ayurveda and Pharma Research, 2020)
An inflammatory condition of male genitalia called Balanoposthitis is made of two words in which Balanitis means inflammation of glans penis and Posthitis means inflammation of prepuce internal part of skin genitalia (prepuce) and is common in uncircumcised population. It primarily occurs due to unretractable foreskin, poor personal hygiene, peeling off of epithelium, secretions from the glands provide damp, warm environment for growth of different organisms which makes the area susceptible for various infections. In the present case study a male patient presented with pain, redness, whitish discharge, greyish-whitish scales over glans penis, mild swelling in groin region and pain in the groin region. It is very much evident that any health issue that affects reproductive organ can also impact various aspects of life, causing anxiety stress, relationship problems or poor self-esteem. But routine examination of penis can create awareness if something wrong is detected. The basic focus of management in Balanoposthitis is to control the acute infection and prevent recurrence along with appropriate hygiene measures. In this case patient of Vat-Pittaj prakruti was successfully managed on Ayurvedic principles, by balancing the vitiated Kapha and Pitta dosha with Shaman chikitsa and encouraging results were found without any untoward effect during the 4 week course of management. Traditional system of medicine is a known wealth of herbs and has potential to manage various ailments of modern era.